Penggunaan Aplikasi Microsoft Office 365 Sebagai Alat Pembelajaran Daring - Wulan Sri Lestari; Hernawati Gohzali; Naca Perangin-Angin (Akademi Farmasi YPPM Mandiri, 2022)
Online learning is a distance learning process through the use of technology that must be done during a pandemic. The ability and skills to use information and communication technology applications are important things that must be possessed by students to be able to follow the learning process well. One of the applications in the field of information and communication technology that has features to support the online learning process is Microsoft Office 365. This application can make it easy for students to collaborate, communicate, share learning documents and view the learning outcomes that have been done. Based on the results of the questionnaire, it was found that the participants had never used Microsoft Office 365 as an online learning medium so they did not have the ability and good skills to utilize the application. To overcome this problem, in this service activity, training on the use of Microsoft Office 365 applications will be carried out in the form of workshops for 2 times and followed by task assignment activities and asynchronous task monitoring on the Microsoft Teams channel that has been determined. Then an evaluation process was carried out by giving pre-test and post-test questions when the training activities were carried out. Based on the results of the pre-test and post-test, it was found that after the training was completed there was an increase in participants' understanding of the use of Microsoft Office 365 applications such as Microsoft Teams, Outlook, OneDrive, Microsoft Forms, Microsoft Stream, Microsoft Office online.